DJ‐1 is not a deglycase and makes a modest contribution to cellular defense against methylglyoxal damage in neurons. Issue 3 (2nd July 2022) - Mazza, Melissa Conti; Shuck, Sarah C.; Lin, Jiusheng; Moxley, Michael A.; Termini, John; Cookson, Mark R.; Wilson, Mark A.
Abstract: Human DJ‐1 is a cytoprotective protein whose absence causes Parkinson's disease and is also associated with other diseases. DJ‐1 has an established role as a redox‐regulated protein that defends against oxidative stress and mitochondrial dysfunction. Multiple studies have suggested that DJ‐1 is also a protein/nucleic acid deglycase that plays a key role in the repair of glycation damage caused by methylglyoxal (MG), a reactive α‐keto aldehyde formed by central metabolism. Contradictory reports suggest that DJ‐1 is a glyoxalase but not a deglycase and does not play a major role in glycation defense. Resolving this issue is important for understanding how DJ‐1 protects cells against insults that can cause disease. We find that DJ‐1 reduces levels of reversible adducts of MG with guanine and cysteine in vitro. The steady‐state kinetics of DJ‐1 acting on reversible hemithioacetal substrates are fitted adequately with a computational kinetic model that requires only a DJ‐1 glyoxalase activity, supporting the conclusion that deglycation is an apparent rather than a true activity of DJ‐1. Sensitive and quantitative isotope‐dilution mass spectrometry shows that DJ‐1 modestly reduces the levels of some irreversible guanine and lysine glycation products in primary and cultured neuronal cell lines and whole mouse brain, consistent with a small but measurable effect on total neuronal glycation burden. However, DJ‐1 does not improve cultured cell viability in exogenous MG. In total, our results suggest that DJ‐1 is not a deglycase and has only a minor role in protecting neurons against methylglyoxal toxicity. Abstract : The neuroprotective protein DJ‐1 has been described as a deglycase that repairs the adducts of methylglyoxal with proteins and nucleic acids. In this study, experiments and kinetic simulation show that DJ‐1's consensus glyoxalase activity explains its in vitro activities, with no need for a deglycase activity. Isotope dilution mass spectrometry of several types of neurons shows that the absence of DJ‐1 results in minor increases in glycation products but does not make cells more vulnerable to methylglyoxal. We conclude that DJ‐1 is a glyoxalase but not a deglycase and makes a minor contribution to neuronal defense against methylglyoxal.